Transglycosylated Starch Modulates the Gut Microbiome and Expression of Genes Related to Lipid Synthesis in Liver and Adipose Tissue of Pigs - Newman, Monica A.; Petri, Renée M.; Grüll, Dietmar; Zebeli, Qendrim; Metzler-Zebeli, Barbara U. (Frontiers in Microbiology, 2018)
Dietary inclusion of resistant starches can promote host health through modulation of the gastrointestinal microbiota, short-chain fatty acid (SCFA) profiles, and lipid metabolism. This study investigated the impact of a transglycosylated cornstarch (TGS) on gastric, ileal, cecal, proximal-colonic, and mid-colonic bacterial community profiles and fermentation metabolites using a growing pig model. It additionally evaluated the effect of TGS on the expression of host genes related to glucose and SCFA absorption, incretins, and satiety in the gut as well as host genes related to lipid metabolism in hepatic and adipose tissue. Sixteen growing pigs (4 months of age) were fed either a TGS or control (CON) diet for 11 days. Bacterial profiles were determined via Illumina MiSeq sequencing of the V3-5 region of the 16S rRNA gene, whereas SCFA and gene expression were measured using gas chromatography and reverse transcription-quantitative PCR. Megasphaera, which was increased at all gut sites, began to benefit from TGS feeding in gastric digesta, likely through cross-feeding with other microbes, such as Lactobacillus. Shifts in the bacterial profiles from dietary TGS consumption in the cecum, proximal colon, and mid colon were similar. Relative abundances of Ruminococcus and unclassified Ruminococcaceae genus were lower, whereas that of unclassified Veillonellaceae genus was higher in TGS- compared to CON-fed pigs (p < 0.05). TGS consumption also increased (p < 0.05) concentrations of SCFA, especially propionate, and lactate in the distal hindgut compared to the CON diet which might have up-regulated GLP1 expression in the cecum (p < 0.05) and mid colon compared to the control diet (p < 0.10). TGS-fed pigs showed increased hepatic and decreased adipocyte expression of genes for lipid synthesis (FASN, SREBP1, and ACACA) compared to CON-fed pigs, which may be related to postprandial portal nutrient flow and reduced systemic insulin signaling. Overall, our data show that TGS consumption may affect gastrointestinal bacterial signaling, caused by changes in gut bacterial profiles and the action of propionate, and host lipid metabolism.